The relationship between principals' instructional leadership behavior and school climate in national secondary schools in Kuala Lumpur / Shazwaatirah Ahamad Walat - Ahamad Walat, Shazwaatirah (2014)
The role of the principal as a key determinant of success in school emerged through leadership practiced. Instructional leadership role is seen as realistic and the indicator for determining the intended educational niche. An active role of principals as instructional leaders tends to improve academic standards in the school (Baharom Mohamad, Mohamad Johdi Salleh & Che Noraini Hashim, 2009). The climate of school where effective teaching and learning occur is also known as a positive school environment. It is the principal's responsibility to build a positive school climate, which provides leadership in developing and maintaining a climate conducive to learning. One factor of school success is the relationship between school climate and leadership behavior (Wheelock, 2005). This study examined the relationship between principal's instructional leadership behavior and the school climate in national secondary schools. The main purpose of the study was to examine the relationship between the principals' instructional leadership behavior and the climate of national secondary schools in Kuala Lumpur. This study also investigated teachers' perception of principals' instructional leadership behavior and school climate based on gender. The Principal Instructional Management Rating Scale - PIMRS (Hallinger, 1983) and Organizational Climate Description Questionnaire for secondary schools (OCDQ-RS) (Hoy, Tarter, and Kottkamp, 1991) were administered to teachers as well as demographic data were collected. The research questions explored teacher's perception of the principal's instructional leadership behavior and school climate. The data collected from 219 National Secondary teachers was analyzed using The SPSS Statistical Package version 20. Descriptive statistics, Pearson Product-Moment Correlation and Independent- Samples t-test was employed. The main findings of the study indicated that statistically significant moderate positive relationships were found between the principal's instructional leadership behavior and the school climate (r = .410, p-value = .000). The study also found significant difference in teachers' perceptions toward principals' instructional leadership behavior and school climate between male teachers and female teachers. The implications of this study reveal that the more engage the principals in instructional leadership behavior, the better the climate of the schools. Finally, several suggestions were made to the program planners, director of the institute, and researchers to improve and enhance the professionalism programs of the principals and school leaders.